EV+A 1998 : Circus ZZ : Exhibition of Visual Art 1998. - Exhibition of Visual + Art Limerick 1998; Murray, Hugh (Limerick : Limerick City Gallery of Art, 1998)
Baker, Robert ; Banahan, Christopher ; Bohanna, Adam ; Bradshaw, Clare ; Brandes, Stephen ; Buckley, Gráinne ; Byrne, Elizabeth ; Byrne, Fergus ; Campion, John ; Carey, Kieran ; Charlesworth, Ian ; Clear, Felicity ; Colbert, Karen T. ; Collins, Michael ; Comerford, Oliver ; Casey, Stephanie Condon ; Considine, Tara ; Coogan, Amanda ; Coote, Melissa ; Cotter, Bernadette ; Daly, Dorothy Ann ; Darke, Colin ; Davenne, Justin P. ; De Fouw, Remco ; Derbyshire, Beth ; MickyDonnelly ; Donovan, Jack ; Doyle, Maria ; Dunne, David ; Dunsmore, Amanda ; Durcan, Sarah ; Fitzgerald, Tom ; Fitzharris, Mike ; Fitzpatrick, Mike ; Foley, Marie ; Fursman, Joanna ; Gannon, Laura ; Geraghty, Suzanne ; Gilligan, Hilary ; Gray, Paul ; Hand, Brian ; Harper, Charles ; Hegarty, Michael ; Hogg, Gavin ; Holten, Katie ; Hopkins, Scott ; Hughes, Ronnie ; Humphries, Tim ; Hunter, Rob ; Reynolds, Patrick Holley & Reynold ; Kelly, Aileen ; Kennedy, Brian ; Kennedy, Edward ; Lagerstrom, Eliz ; Lewis, Róisin ; Lilburn, David ; Lindsay, Namara ; Linehan, Aidan ; Llewellyn, Edin ; Lynch, Catherine M. ; Lyons, Deirdre ; McAllister, Terry ; McCann, Leo ; McCarthy, Brigid ; McCarthy, Danny ; McCarthy, Eoin ; McDonald, Fiona ; MacGabhann, Don ; McNulty, Margo ; MacWilliam, Susan ; Martin, Fergus ; Merriman, Julie ; Miller, Nick ; Mooney, Breeda ; Morgan, Deirdre ; Morgan, Peter ; Mosse, Paul ; Nicolaou, Nicos ; Nolan, Collette ; Nolan, Isabel ; Fitzgerald, Abigail O'Brien & Peter ; O'Connor, Maureen ; O'Dea, Michael ; O'Donoghue, Alice ; O'Mahony, Deirdre ; O'Rourke, Seamus ; Peat, Louise ; Dingilian, Alan Phelan & Jim ; Philipsz, Susan ; Ryan, Robert ; Scattergood, Francis ; Slade, Richard ; Smyth, Bernard ; McGovern, Amelia Stein & Barry ; Stewart, Beatrice ; Timmons, David ; Walker & Walker ; etc.
biografie
EV+A 1998 : Circus ZZ, 1998
Engels
boek